Peningkatan Self-Confidence Siswa Dalam Berbicara Bahasa Inggris Melalui Class-Based Assessment Di Smp Negeri 2 Galesong Selatan - Maudy Anastasya Maudy; Ainurrahma Syahrani; Ummi Khaerati Syam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe how Class-Based Assessment improves students’ self-confidence in speaking English. Using a qualitative descriptive method, nine students of Class VIII B at SMP Negeri 2 Galesong Selatan participated in the research. Data were collected through interviews and open-ended questionnaires. The results show that most students initially felt nervous, shy, and afraid of making mistakes when speaking English. After the implementation of Class-Based Assessment, students became more confident, active, and motivated. Continuous practice, positive thinking, and support from teachers and peers helped reduce their anxiety. Overall, Class-Based Assessment effectively increased students’ self-confidence and created a more enjoyable and interactive English learning environment.